IMPACT OF GLOBALISATION ON TRIBALS IN KERALA (International Journal of World Research, 2014)
Globalisation is the integration of Economic, political and cultural systems across the globe through interactions between nations, with the economic perspective government policies around the globe that have opened economies domestically and internationally, aided by technological development have spurred increases in cross boarder trade, investment and migration so large that many observers believe the world has enter a qualitatively new phase in its economic development. But there are sharp differences on its impact on society. The Indian state of Kerala have had entirely different experience of development process from anywhere else in the country, the much celebrated Kerala model of development has faced enough criticism for excluding the tribals, Dalits, fisher folks and other weaker sections of the state. The present paper argues that It is been accepted that the celebrated kerala model of development has not made much changes for the socio-economic life of the tribals of kerala, by using different secondary data sets the paper argues that after the sixty years of formation of the state tribals continues as one of the most marginalised community within the state, the post globalised developmental projects and developmental dreams of the state has again made the deprivation of the tribals of kerala and the developmental divide has increased between the tribal and non-tribal in the state